…0.167emBecause the homeland cannot be in opposition: analysing the discourses of Fidesz and Law and Justice (PiS) from opposition to power - Seongcheol Kim (East European Politics, 2021)
Drawing on Ernesto Laclau's theory of discourse, hegemony, and populism, this paper analyses the development of the discourses of Fidesz in Hungary and Law and Justice (PiS) in Poland from opposition to power with a focus on how authoritarianism is articulated, especially in relation to populism. The post-foundational discourse analysis finds that populism takes on an authoritarian expression only in certain discursive combinations, mostly with nationalism, while authoritarianism follows a range of different logics (populist and non-populist alike), including nationalism and social welfarism without populism (PiS) or what Laclau refers to as institutionalism (Fidesz).
Keywords: 330; authoritarianism; Hungary; nationalism; Poland; political parties; populism